2012
DOI: 10.1007/s12609-012-0085-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mammography versus Magnetic Resonance Imaging for Breast Cancer Screening

Abstract: Mammographic screening has been proven to detect breast cancer at an early stage and to reduce mortality from breast cancer. Nevertheless, some limitations concerning sensitivity, as well as adverse effects such as false negatives and radiosensitivity, has led to a need to search for other screening techniques. Magnetic resonance imaging has been an excellent choice for some specific subgroups, including patients at high risk. However, high cost, low availability, and lack of long-term trials aiming to prove t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…This association is also mentioned by [9]. While another study reported by [10] that is worthwhile to begin screening for women with a high risk from the age of 30 or 35 years old.…”
Section: Discussionmentioning
confidence: 57%
“…This association is also mentioned by [9]. While another study reported by [10] that is worthwhile to begin screening for women with a high risk from the age of 30 or 35 years old.…”
Section: Discussionmentioning
confidence: 57%